Molecular Transistor Controlled through Proton Transfer - Weckbecker, Dominik; Coto, P. B.; Thoss, M. (Journal of Physical Chemistry Letters, 2021)
The potential of proton transfer reactions as a fundamental mechanism to realize a nanoscale molecular transistor is investigated. Employing density functional theory and the nonequilibrium Green's function formalism, we identify molecule-graphene nanojunctions, which exhibit high- and low-conducting states depending on the specific location of protons in the molecular bridge. In addition, we show that an electrostatic gate field can control the proton transfer process and thus allow specific conductance states to be selected. In this way, the current in the junction can be switched on and off as in a field-effect transistor. The underlying mechanism is analyzed in detail.
CRIS-Team Scopus Importer:2021-01-15